COVID-19 and Corporate Governance Performance: Beyond the Financial Metrics (2021)
Corporate governance and, more broadly, the performance of corporate boards have traditionally been measured using financial metrics. These financial metrics such as Return on Investment (ROI), Return on Assets (ROA), Return on Equity (ROE), Earnings and Profitability Ratio (E and P) are ex post measure of organizations performance arising from corporate board activities. These financial metrics are largely one-dimensional measure of corporate performance and do not fully account for the other dimensions of organization responsibilities. The COVID-19 and the changing organizational dynamics have made the case for corporate board’s performance to be assessed beyond the usual financial metrics. In this study, we provide a framework that accounts for the various dimensions of organization activities: finance, social and environmental, the Triple-Bottom (TBL) approach. A TBL-compliance metric was constructed, which tracked the performance of selected manufacturing firms in Nigeria using a content analytical technique. The result showed that the majority of the firms performed remarkably well in areas of profitability and economic value creation but less satisfactorily inareas of social and environmental sustainability. On aggregate, the sampled firms committed less than 1% of their profit after tax on corporate social responsibility, while less than 5% of the sampled firms scored above average on the TBL-adoption matrix.